RECREATIONAL FACTOR IN ARCHITECTURAL PLANNING ORGANIZATIONS OF RIVERSIDE SPACE - Самойленко, Евгения (SWorldJournal, 2020)
Abstract. Riverside areas are becoming one of the most attractive urban areas, characterized by the saturation of various functional zones and their frequent change. Renovation in the field of functional conflict involves a comprehensive approach to the f